Anfis model for the simulator of the dynamic behavior of a fed batch bioreactor built from the proposed model to observe the oscillating behavior of the zymomonas mobilis - Sandoval Z., Marcelo Francisco (2009)
This paper explains the simulator of dynamic behavior of a Fed Batch bioreactor modeled with anfis networks. The simulator was built from the proposed model to observe the oscillatory behavior of the Zymomonas mobilis (Z.m). The model uses the anfis networks created in Matlab to simulate the system response. The commands genfis1 and genfis2 were used to generate the structure of the fuzzy inference system without using data grouping and with data grouping respectively. The predictions of the Anfis network are shown in the results for the output system variables: the biomass concentration, the substract concentration, the product concentration and the biomass growth speed.